Differential quantification of isobaric phosphopeptides using data-independent acquisition mass spectrometry. Issue 8 (15th June 2016) - Sidoli, Simone; Fujiwara, Rina; Kulej, Katarzyna; Garcia, Benjamin A.
Abstract : Data-independent acquisition (DIA) is here applied to determine unexplored phosphorylation events on isobarically modified peptides. Abstract : Phosphorylation is a post-translational modification (PTM) fundamental for processes such as signal transduction and enzyme activity. We propose to apply data-independent acquisition (DIA) using mass spectrometry (MS) to determine unexplored phosphorylation events on isobarically modified peptides. Such peptides are commonly not quantitatively discriminated in phosphoproteomics due to their identical mass.